Pelatihan Kader Posyandu untuk Pendampingan Korban Kekerasan Seksual di Kelurahan Banjar Kecamatan Ampenan Kota Mataram - Pujiarohman, Pujiarohman; Herlina, Lenny; Syamsun, Arfi; Harahap, Ida Lestari; Pramesti, Evane Dyahayu; Wahid, Lalu Abdurrachman (Al-DYAS, 2025)
Sexual violence in Indonesia has increased significantly, both in terms of quantity and quality. Through a report from the Ministry of Women's Empowerment and Child Protection (KemenPPPA), more than 9,600 cases of violence against children were recorded in the period from January to May 2023. This increasing trend is largely due to the increasing courage of victims to report the incident. The main focus of this case is sexual violence, which includes rape, molestation, and sexual exploitation. West Nusa Tenggara (NTB), as an example, recorded 188 cases of sexual violence against children in 2021-2022, with types of incidents including rape and molestation. Involving various impacts, sexual violence damages the physical, emotional, and psychological aspects of the victim. Serious handling and in-depth understanding from various sectors are key to overcoming this problem. The involvement of Posyandu as a public health institution is a proactive solution to provide support and assistance to victims of sexual violence. Through training of Posyandu cadres in Banjar Village, Ampenan District, it is hoped that a responsive support network can be formed to address the issue of sexual violence at the community level. Collaboration with health, child protection, and mental health institutions is an integrated step that supports victim recovery. This service contributes to the understanding of the importance of the role of Posyandu in dealing with sexual violence and details the impacts and concrete solutions to improve prevention and recovery. The conclusions of this study provide a deeper understanding of the complexity of the issue of sexual violence and provide a basis for policy recommendations to improve the community approach in addressing this problem.